2022
DOI: 10.3390/nu14245281
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin Reversed Long-Term N-methyl-N-nitro-N-Nitroguanidine Exposure Induced EMT and Cell Proliferation by Activating Autophagy in Gastric Tissues of Rats

Abstract: Gastric cancer is a common malignant tumor worldwide. N-methyl-N-nitro-N-nitroguanidine (MNNG) is one of the most important inducing factors of gastric cancer. Autophagy can affect the occurrence and development of gastric cancer, but the mechanism is not clear. Chemoprevention has been shown to be a rational and very promising approach to the prevention of gastric cancer. Hesperidin is a citrus flavone, an abundant polyphenol in citrus fruits and traditional Chinese medicine. It has an excellent phytochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“… [ 181 ] Gastric cancer Hsd MNNG-induced rats Activate autophagy and the PI3K/AKT pathway. [ 182 ] Esophageal cancer Hst Eca109 cells Human xenograft tumor nude mice Depletion of GSH, accumulation of ROS, increase of cleaved caspase-9 and cleaved caspase-3 [ 183 ] Ehrlich ascites carcinoma Hsd Ehrlich ascites carcinoma (EAC) mice Down-regulate Bcl2 and Stimulate Caspase3 and Bax genes expression [ 184 ] Liver cancer Hsd DEN/CCl4-induced rats Activate Nrf2/ARE/HO-1 and PPARγ pathways. [ 185 ] Gastric cancer Hsd Xenograft tumor nude mice Activate the mitochondrial pathway by increasing the ROS.…”
Section: Biological Activities Of Hsd and Hstmentioning
confidence: 99%
“… [ 181 ] Gastric cancer Hsd MNNG-induced rats Activate autophagy and the PI3K/AKT pathway. [ 182 ] Esophageal cancer Hst Eca109 cells Human xenograft tumor nude mice Depletion of GSH, accumulation of ROS, increase of cleaved caspase-9 and cleaved caspase-3 [ 183 ] Ehrlich ascites carcinoma Hsd Ehrlich ascites carcinoma (EAC) mice Down-regulate Bcl2 and Stimulate Caspase3 and Bax genes expression [ 184 ] Liver cancer Hsd DEN/CCl4-induced rats Activate Nrf2/ARE/HO-1 and PPARγ pathways. [ 185 ] Gastric cancer Hsd Xenograft tumor nude mice Activate the mitochondrial pathway by increasing the ROS.…”
Section: Biological Activities Of Hsd and Hstmentioning
confidence: 99%
“…MNNG can induce gastric cancer by regulating inflammation, cell damage, cell differentiation mitochondrial dysfunction, glycolysis pathogenesis and oxidative stress processes ( Cai et al, 2018 ; Zhao et al, 2019a ; Cai et al, 2019 ; Cui et al, 2021 ; Wen et al, 2021 ; Gunes-Bayir et al, 2022 ). MNNG promotes the occurrence and development of gastric cancer by regulating processes such as autophagy, EMT, apoptosis, proliferation, angiogenesis, gastric epithelial dysplasia, malignant transformation and change endogenous metabolites ( Zhao et al, 2019b ; Deng et al, 2019 ; Wu and Hui, 2020 ; Liang et al, 2022a ; Cai et al, 2022 ; Chen et al, 2022 ; Peng et al, 2022 ; Yang et al, 2022 ; Xie et al, 2023 ).Therefore, there is an urgent need to find an effective and low side effect intervention or treatment strategy. In recent years, phytochemicals and active ingredients of herbal medicine have showed excellent application prospects in the prevention and treatment of gastric cancer.…”
Section: Effects Of N-nitrosamines and Mnng On The Occurrence And Pro...mentioning
confidence: 99%
“…A large number of studies have showed that phytochemicals play a very important intervention effect on gastric cancer ( Mao et al, 2020 ; Liang et al, 2022a ; Zhao et al, 2023 ). The effects of phytochemicals on the treatment and prevention of MNNG exposure related gastric cancer also have been studied.…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 99%
See 2 more Smart Citations